Collinin Reduces Porphyromonas gingivalis Growth and Collagenase Activity and Inhibits the Lipopolysaccharide‐Induced Macrophage Inflammatory Response and Osteoclast Differentiation and Function. Issue 5 (1st May 2013) - Santos, Juliana; Marquis, Annie; Epifano, Francesco; Genovese, Salvatore; Curini, Massimo; Grenier, Daniel
Abstract : Background: Collinin is a secondary plant metabolite belonging to the class of geranyloxycoumarins. We explored the potential beneficial impact of collinin on periodontal health by investigating its effect on Porphyromonas gingivalis ( P. gingivalis ), lipopolysaccharide (LPS)‐induced inflammatory response of macrophages, and osteoclastogenesis. Methods: Collinin was synthesized from pyrogallol and propiolic acid. A microdilution assay was used to determine antibacterial activity of collinin. The effect of collinin on collagenase activity of P. gingivalis was determined using fluorescent collagen. Macrophages were treated with collinin before being stimulated with LPS. The secretion of interleukin‐6, chemokine (C‐C motif) ligand 5, and prostaglandin E2 was assessed by enzyme‐linked immunosorbent assays (ELISA). The inhibitory effect of collinin on differentiation of human preosteoclastic cells was assessed by tartrate‐resistant acid phosphatase staining, whereas the secretion of matrix metalloproteinase‐9 (MMP‐9) was measured by ELISA. Bone resorption activity was investigated by using a human bone plate coupled with an immunoassay that detected the release of collagen fragments. Results: Collinin inhibited the growth of P. gingivalis . The effect was more pronounced under iron‐restricted conditions. Collinin dose dependently inhibited the degradation of type I collagen by P. gingivalis . It was also a potent inhibitor of the LPS‐induced inflammatory response in macrophages and completely inhibited receptor activator of nuclear factor κB ligand‐dependent osteoclast differentiation and MMP‐9 secretion. Last, collinin affected bone degradation mediated by mature osteoclasts by significantly decreasing the release of collagen helical peptides. Conclusion: Although clinical trials are required, data from these in vitro analyses support the potential of collinin as a therapeutic agent for treating inflammatory periodontitis associated with bone breakdown.